Generation X Goes Global. - Henseler, Christine (Routledge research in cultural and media studies., 2012)
This edited volume is the first book of its kind to engage critics' understanding of Generation X as a global phenomenon. Citing case studies from around the world, the research collected here broadens the picture of Generation X as a demographic and a worldview. The book traces the global and local flows that determine the identity of each country's youth from the 1970s to today. Bringing together twenty scholars working on fifteen different countries and residing in eight different nations, this book present a community of diverse disciplinary voices. Contributors explore the converging prop.